INDIA’S STRATEGIC PRESENCE AMID GROWING CHINESE INFLUENCE IN SRI LANKA: IN THE CONTEXT OF THE MODI REGIME. - Tiwari, Sachin; Meena, Vikash Kumar; Tomar, Shashank (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Sri Lanka, located in the Indian Ocean to the south of India, is an island nation which has a rich and glorious past. It has centuries-old cultural, religious and social relations with India. India and Sri Lanka are closely connected to each other’s life traditions and values. At the core of which is the centuries-old belief in Buddhism and Hinduism and shared cultural heritage. Both countries, having shared the experience of colonialism, give an important place to non-alignment and independent decision in their foreign policy. Promotion of their respective national interests, India’s concern over questions related to the rights of expatriate citizens, especially Tamils ​​living in Sri Lanka, China’s growing role in South Asia, rights over marine resources etc. have been influencing the relationship between the two countries. Due to its geographical location, Sri Lanka holds an important place in India’s security purposes. In the 21st century, Sri Lanka has special importance for both India and China. India’s current foreign policy towards Sri Lanka, which holds an important place in Indian foreign policy, is keeping in mind the growing influence of China in Sri Lanka. In this article we will mainly study the current state of India Sri Lanka relations during the rule of Narendra Modi in India and the role of China as an influential power.